Comparing the information security culture of employees who had read the information security policy and those who had not: Illustrated through an empirical study. (13th June 2016) - Da Veiga, Adéle
Abstract : Purpose: This study aims, firstly, to determine what influence the information security policy has on the information security culture by comparing the culture of employees who read the policy to those who do not, and, secondly, whether a stronger information security culture is embedded over time if more employees have read the information security policy. Design/methodology/approach: An empirical study is conducted at four intervals over eight years across 12 countries using a validated information security culture assessment (ISCA) questionnaire. Findings: The overall information security culture average scores as well as individual statements for all four survey assessments were significantly more positive for employees who had read the information security policy compared with employees who had not. The overall information security culture also improved from one assessment to the next. Research limitations/implications: The information security culture should be measured and benchmarked over time to monitor change and identify and prioritise actions to improve the information security culture. If employees read the information security policy, it has a positive influence on the information security culture of an organisation. Practical implications: Organisations should ensure that employees have read the information security policy to aid in minimising the human risk, related errors and incidents and, ultimately, to instil a stronger information security culture with a higher level of compliant behaviour. Originality/value: This research confirms theoretical research indicating that the information security policy could influence the information security culture positively. It provides novel and statistical evidence illustrating that if employees read the information security policy, they have a stronger information security culture and that the culture can be improved through targeted interventions using an ISCA.